Analisis Likuiditas Terhadap Harga Saham Perusahaan Telekomunikasi dalam Kondisi Financial Distress : Bursa Efek Indonesia 2009-2013 - Gunarsih Gunarsih; Daryanto Hesti Wibowo (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2014)
The research analyzes the influence of liquidity consisting of CR and DER ratio of stock prices. This study uses financial ratio analysis and multiple regression analysis. The results of multiple regression analysis with the test statistic F variables CR and DER showed together had effect on stock prices. Similarly, the partial variable CR had effect on stock prices, because tcount ≥ ttable , and variable DER had no effect on stock prices, because tcount ≤ ttable .